KEGIATAN ARUNG JERAM SEBAGAI SARANA PEMBENTUKAN TEAM COHESION MAHASISWA PENDIDIKAN JASMANI UNIVERSITAS MUHAMMADIYAH SURAKARTA - Agus Widya Purnomo; Gatot jariono; Eko Sudarmanto; Nurhidayat Nurhidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the role of rafting activities as an experiential learning medium in fostering team cohesion among Physical Education students at Universitas Muhammadiyah Surakarta. The research employed a quantitative descriptive design involving 81 students from the 2022 cohort who participated in rafting activities at the Upper Progo River, Magelang, Indonesia, in 2025. Data were collected using a structured questionnaire based on the Group Environment Questionnaire (GEQ), measuring task cohesion and social cohesion dimensions. Descriptive statistics and Pearson correlation analysis were applied to analyze the data. The results indicate that the overall level of team cohesion was categorized as very high, with mean scores ranging from 4.31 to 4.72 on a five-point Likert scale. A total of 77.3% of respondents fell into the very high category, while 22.7% were classified as high, with no respondents in the moderate or lower categories. Correlation analysis revealed significant positive relationships among GEQ indicators, ranging from weak to very strong (r = 0.19–0.77, p < 0.05), demonstrating a strong interconnection between task cohesion and social cohesion. These findings suggest that rafting activities create a structured experiential environment that enhances communication, trust, coordination, and social bonding within student groups.